Exploring supply chain deception, sustainability, and customer perceptions - Hammadi, Adil; Taylor, Ruth; Reiners, Torsten (2018)
© 2018, Curran Associates Inc. All rights reserved. Cases like Dieselgate and Takata airbag revealed the widespread use of deception throughout the industry. With common expectations like green-and blue-washing, we did not envisage this behaviour with organisations known for their organisational culture based on strong ethics and values. To operationalise sustainability in the context of supply chain, we adopted the sustainability practices of the organisation and current established supply chain deception concepts from the literature in relation to the downstream supply chain – the consumer-and examined how the severity of deception impacts the TBL and consumers’ perception of the organisation. In this paper, we introduce the Deception Impact Model (DIM) connecting the three dimensions severity of deception, implementation of sustainability practices, and impact of customers to reflect on the behaviour and organisational culture and the possible implications of their deceptive activities; demonstrating that Donald Trump is merely a transition away from Robin Hood.